Analysis of Factors Affecting Economic Growth in Underdeveloped Regions in Indonesia - M. Atras Teralsyah; Arivina Ratih Yulihar Taher (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to examine the effect of Village Fund Allocation (ADD), Gross Fixed Capital Formation (PMTB) and Labor Force Participation Rate (TPAK) on Economic Growth in 62 Disadvantaged Regions in Indonesia. The research sample covers 62 Disadvantaged Regions in Indonesia according to PEPRES RI Number 63 of 2020-2024, the period from 2016 to 2020. The panel regression method uses the Fixed Effect model to investigate the influence of Village Fund Allocation (ADD), Gross Fixed Capital Formation (PMTB)) and Labor Force Participation Rate (TPAK) on the Economic Growth of 62 Underdeveloped Regions in Indonesia. The results showed that the village Fund Allocation (ADD) variables and Gross Fixed Capital Formation (PMTB) respectively had a positive and significant influence on the Economic Growth of 62 Disadvantaged Regions in Indonesia, while the Labor Force Participation Rate (TPAK) variable had a positive but not significant to the Economic Growth of 62 Disadvantaged Regions in Indonesia.